Effects of Flame Retardant Additives on Fire Properties of Paraffin Impregnated Gypsum - Iskandar Syah, Nur Izzah Nadiah; Md Said, Mohamad Syazarudin (John Wiley and Sons Inc, 2025)
Phase change material (PCM) can be integrated into construction materials to mitigate temperature fluctuations and enhance thermal mass. However, their incorporation may increase the combustibility of these materials. This study investigates the fire performance of gypsum boards impregnated with paraffin-based phase change material (RT20) and various flame retardant additives, including ammonium polyphosphate (APP), montmorillonite (MMT), and pentaerythritol (PER). Cone calorimeter tests were conducted to evaluate ignitability, heat release, mass loss, smoke production, and gas emissions. The gypsum + RT20 sample exhibited a time to ignition (TTI) of 31 s. Incorporation of APP reduced the TTI to 27 s, while the combination of APP, MMT, and PER further reduced TTI to 21 s. The maximum heat release rate (HRR) increased from 7.58 kW/m2 (gypsum + RT20) to 28.72 kW/m2 (gypsum + RT20 + APP), but decreased to 5.42 kW/m2 with the addition of MMT and PER. Total heat release (THR) followed a similar trend. The peak specific extinction area (SEA) increased to 487.08 m2/kg with APP but was reduced to 259.24 m2/kg when MMT and PER were added. Carbon monoxide and carbon dioxide yields showed variability across formulations. The fire growth rate index (FIGRA) and maximum average rate of heat emission (MARHE) were lowest (0.0098 kW/m2 · s and 1.9 kW/m2, respectively) in the gypsum + RT20 + APP + MMT + PER sample, indicating comparatively lower fire growth and heat release characteristics. These findings emphasize the importance of optimizing flame retardant formulations to achieve both effective fire resistance and minimal smoke hazards.